STRATEGIES FOR HANDLING FRAUD CASES AGAINST CUSTOMERS IN BSI KCP SITUBONDO SERVICES - Lina Wati (IJED: International Journal of Economy Development Research, 2024)
Fraud is a crime that harms many parties, including Bank Syariah Indonesia (BSI) as a financial institution. Fraud against customers is a serious threat to Bank Syariah Indonesia and requires an effective handling strategy. From the above statement, this research aims to find out and analyze the motives of banks in fraud cases, besides that this research also analyzes banks' efforts in improving service quality with customer satisfaction and also how customers perceive the handling of fraud cases. This study uses a qualitative descriptive method of phenomenology. In accordance with the focus of the study in the study, the data mining process is carried out by means of a descriptive qualitative approach, data collection techniques in the research using observation, interview, and documentation methods and then analyzed using descriptive qualitative. From the results of the above data, it can be concluded that Bank Syariah Indonesia (BSI) has implemented a prevention strategy that involves educating customers about fraud risks, detection through transaction monitoring, and handling fraud cases by involving internal investigations and cooperation with authorities. By implementing this strategy comprehensively and it is expected that BSI can protect its customers from fraud threats and increase customer trust. The steps to protect yourself from fraud are 4 dimensions, including verification of communication, using official sources, paying attention to accounts, and protecting personal information. In general, customers are satisfied with the existence of CHMS (Complaint Handling System) which is an application about customer complaints that have cases.